An observational comparative study to evaluate the use of image-guided surgery in the management and outcome of supratentorial intracranial space-occupying lesions - Ashis Patnaik; N Guruprasad; Arunkumar Sekar; Sumit Bansal; Rabi N Sahu (Wolters Kluwer Medknow Publications, 2024)
Objectives: The objective of this article is to study the effect of neuronavigation on the outcome of surgery for supratentorial tumors, such as the extent of resection, size of craniotomy, and overall morbidity and mortality by comparing with conventional excision. Methods: A total of 50 patients undergoing intracranial surgery for supratentorial space-occupying lesions from 2020 to 2022 were included in the study. One intervention group consisted of patients undergoing surgical resection of supratentorial tumors utilizing image guidance versus the control group, which consisted of patients undergoing surgical excision of supratentorial tumor excision without image guidance. Parameters used to compare the outcome were the extent of resection of the lesions, craniotomy size, and overall morbidity and mortality. Results and Conclusion: There was no significant reduction in craniotomy size or prolongation of operative duration with the use of neuronavigation. There was no significant difference in postoperative hospital stay between the two groups. Neuronavigation-assisted cases did not show any significant reduction in the occurrence of postoperative neurological deficits or any reduction of overall morbidity and mortality.